Evolução microestrutural e propriedades mecânicas das ligas Al-10%Si-0,45%Mg e Al-10%Si-1,0%Mg - Gandolfi, Maressa (2021)
Al-Si alloys with high silicon (Si) content are widely used in aerospace, automotive, microelectronics, among others. In this context, the Al-10 wt.% Si alloys with the addition of Magnesium (Mg) are alternatives that arouse interest for processing in permanent molds, by lost wax, by high pressure die-casting and by additive manufacturing. Due to growing interest, there are necessary more in-depth studies of the interrelationships between solidification thermal parameters, microstructural parameters and mechanical properties of the Al-10 wt. % Si-Mg alloys, both due to the scarcity of these data in the literature and due to the importance of this knowledge in the pre-programming related to foundry processes. In this sense, a study for the conditions of slow and moderate solidification was carried out through this Master's proposal. Through transient directional solidification experiments a wide range of dendritic scale variation was obtained for both Al-10 wt.% Si-0.45 wt.% Mg and Al-10 wt.% Si-1.0 wt.% Mg alloys, with primary and secondary dendritic spacings, 1 and 2 ranging from 76 m to 360 m and from 17 m to 38 m, respectively. The interdendritic phases detected were Mg2Si with Chinese Script morphology and Si with lamellar morphology, with a higher fraction of Mg2Si for the alloy containing 1.0 wt.% Mg. Thanks to the higher fraction of refined Mg2Si particles, in addition to greater refining and complexity of the dendritic network (smaller 2), the Al-10 wt.% Si-1.0 wt.% Mg alloy achieved greater mechanical strength and ductility compared to the Al-10 wt.% Si-0.45 wt.% Mg alloys. The samples of the Al-10 wt.% Si-1.0 wt.% Mg alloy with 2 of 16 m show the best balance of tensile properties with ultimate tensile strength limit of 220 MPa, yield tensile strength of 142 MPa and elongation-to-fracture of 5%.